Thermopower and magnetotransport properties of Bi100−xSbx topological insulator thin films prepared by flash evaporation - Osmic, E. (2022)
We have measured the temperature dependence of resistance R(T), thermopower S(T), magnetoresistance (MR) and the Hall effect (HE) of Bi80Sb20, Bi85Sb15 and Bi90Sb10 topological insulator thin films. Samples were prepared by sequential flash-evaporation at room temperature and annealing at T = 350 K. The R(T) of the three investigated samples show metallic-like behavior at temperatures less than T = 75 K, while at higher temperatures, R(T) curves show a semiconducting-like behavior. The thermopower S(T) of the three investigated samples is negative in the entire temperature range measured in this work, with a linear behavior from 5 K up to ≈100 K. The magnetoresistance of all samples is positive with a small temperature dependence. The highest MR(B = 7 T) was observed in Bi85Sb15 with a ≈600% and ≈125% change at 5 K and 300 K, respectively. Clear evidence of weak antilocalization contribution to the MR was observed only in sample Bi85Sb15 at temperatures T < 75 K. Quantum oscillations in the MR originating from the Fermi surface, which has a clear two-dimensional character, were observed in sample Bi85Sb15 up to ≈21 K. Carrier mobility information of sample Bi85Sb15 was extracted from low field HE data, showing a remarkably high value of μ ≈ 2.8 × 104 cm2/Vs at 5 K, with a small decrease for increasing temperature.